Draw the line - Linn, Laurent (Margaret K. McElderry Books, 2016)
Adrian Piper may be a talented artist, a sci-fi geek, and gay, but at his Texas high school those traits would only bring him the worst kind of attention. He is only free to express himself is at his drawing table, crafting a secret world through his own Renaissance-art-inspired superhero, Graphite. After a hate crime occurs Adrian must discover his own power, decide how to use it, and know where to draw the line-- no matter how dangerous the risk.